2019
DOI: 10.1097/brs.0000000000003191
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Stand-alone Lateral Lumbar Interbody Fusion Versus Open Laminectomy and Posterolateral Instrumented Fusion in the Treatment of Adjacent Segment Disease Following Previous Lumbar Fusion Surgery

Abstract: Study Design. Retrospective cohort study. Objective. The aim of this study was to compare clinical and radiographic outcomes of patients who underwent stand-alone lateral lumbar interbody fusion (LLIF) to those who underwent posterolateral fusion (PLF) for symptomatic adjacent segment disease (ASD). Summary of Background Data. Recent studies have suggested that LLIF can successfully treat ASD; however, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…LLIF was developed as a minimally invasive alternative for interbody fusion that can potentially avoid the approachrelated complications associated with anterior and posterior direct approaches. 1 Recent studies have demonstrated improved clinical and radiographic outcomes in patients undergoing LLIF for degenerative pathology 2,[18][19][20][21] ; however, this minimally invasive technique has resulted in a new set of approach-related nerve complications during interbody fusion as a result of traversing of the psoas muscle, which contains the lumbar plexus. 3,4,[8][9][10] The high incidence of nerve injury after LLIF resulted in several studies attempting to use IONM to minimize the risk of lumbar plexus injury.…”
Section: Discussionmentioning
confidence: 99%
“…LLIF was developed as a minimally invasive alternative for interbody fusion that can potentially avoid the approachrelated complications associated with anterior and posterior direct approaches. 1 Recent studies have demonstrated improved clinical and radiographic outcomes in patients undergoing LLIF for degenerative pathology 2,[18][19][20][21] ; however, this minimally invasive technique has resulted in a new set of approach-related nerve complications during interbody fusion as a result of traversing of the psoas muscle, which contains the lumbar plexus. 3,4,[8][9][10] The high incidence of nerve injury after LLIF resulted in several studies attempting to use IONM to minimize the risk of lumbar plexus injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to avoiding these complications, the LLIF can address underlying foraminal and central stenosis via indirect decompression [8, 19]. Recent studies have demonstrated the capabilities of lateral interbody fusion in the treatment of ASD [6, 20-21]. LLIF is an attractive alternative in treating ASD due to limited blood loss, no need to reexplore previous laminectomies, and an overall reduction in complications [6].…”
Section: Discussionmentioning
confidence: 99%
“…2) Type of surgery is a procedure or a method that is used to treat or remove the pathology from the lumbar site. Recently, there have been many types of minimal invasive method to overcome degenerative lumbar illness, such as MIS-TLIF, Endo-LIF, UBE, LLIF and so on [36] for open procedures such as TLIF, PLIF. As we know that minimal invasive technique has the lower outcome of SSI compared to routine technique.…”
Section: Surgical-related Risk Factorsmentioning
confidence: 99%